SIMULAÇÃO COMO FERRAMENTA PARA GESTÃO LOGISTICA EM CANTEIRO DE OBRAS: UM ESTUDO DE CASO EM TRANSPORTE DE ARMADURAS - Fernandes, Luara Lopes de Araujo; Costa, Dayana Bastos; Pérez, Cristina Toca (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Logistical planning is still a neglected step, despite it establishes conditions for the effectiveness of the production process. Anticipation in the decision-making process and improvements in logistic can provide competitive advantage for construction companies. This study focuses on the evaluation of the potential of improvements that the simulation tools can provide for logistic management on construction sites. The paper is based on two simulation tests carried out on two income housing project sites. The simulation models were developed in Arena software. As main results of this study, data of transportation times and models animations were obtained, allowing a better visualization of the process, which may assist, in future projects, managers in the decision-making process.